Pengaruh kepemilikan majerial,kepemilikan institusional, kualitas audit dan intelektual capital terhadap integritas laporan keuangan - Pronika Pronika; Anisa Kusuma Wardani (Worksheet : Jurnal Akuntansi, 2026)
Financial statement integrity is an important indicator of the quality of financial reporting, as it reflects the reliability and honesty of accounting information presented by companies. Low financial statement integrity can reduce stakeholder trust and increase the risk of inappropriate decision-making. This study aims to examine the effect of managerial ownership, institutional ownership, audit quality, and intellectual capital on financial statement integrity. This research employs a quantitative approach using secondary data obtained from the annual financial statements of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The sample was selected using a purposive sampling method based on predetermined criteria. Financial statement integrity is measured using accounting conservatism, managerial ownership and institutional ownership are measured by the percentage of share ownership, audit quality is measured based on public accounting firm affiliation, and intellectual capital is measured using the Value Added Intellectual Coefficient (VAIC) method. Data analysis was conducted using multiple linear regression, accompanied by classical assumption tests and hypothesis testing. The results indicate that managerial ownership and institutional ownership have a positive effect on financial statement integrity, suggesting that ownership structure plays an effective monitoring role over management. Audit quality also has a positive effect on financial statement integrity, reflecting the role of independent auditors in enhancing the credibility of financial reports. Furthermore, intellectual capital has a positive effect on financial statement integrity, indicating that effective management of intellectual assets contributes to improving the quality of corporate financial information. Keywords: managerial ownership, institutional ownership, audit quality, intellectual capital, financial statement integrity.